Нотатки про вбрання середньовічного селянства (із досліджень 2007—2011 рр. поселення Ходосівка-Рославське) - Готун, І.А.; Гунь, М.О.; Сухонос, А.М. (Археологія і давня історія України, 2021)
Розташоване у південних передмістях Києва
поселення давньоруського періоду та монгольськолитовської доби Ходосівка-Рославське привернуло
увагу високорозвиненим багатогалузевим господарством і значним рівнем добробуту мешканців з
першого сезону розкопок. Післяпольове опрацювання
результатів перших п’яти років досліджень пункту дозволило характеризувати різні сторони матеріальної і простежені за матеріальними залишками елементи духовної культури його населення,
чому присвячено низку публікацій. Предметом чергової з них постали виявлені за названий період артефакти, що вказують на особливості вбрання та прикрас давніх мешканців цього осередку. Незначне,
на перший погляд, число відповідних знахідок, тим не менше, дозволило відзначити доволі оригінальні
риси цієї пам’ятки та вкотре наголосити на невичерпаних інформаційних можливостях неукріплених поселень середньовічної доби. In spite of the parity relations between the medieval
towns and their country surroundings and the
high level of development of the settlement structures
tracked during the wide-scale research of the settlements
of the Southern Russ, the new excavations in
the non-fortified settlements keep brining certain discoveries.
This is remarkable at Khodosivka-Roslavske
settlement found by the Northern Expedition in 2007.
The working over of the results of the excavations in
2007—2011 allowed testify highly-developed household
and significant level of the inhabitants’ wellbeing.
Some peculiarities of the inhabitants’ material culture
were characterized, a regular publication was devoted
to the specifics of their outfit.
The collected spindles and weights for weaving allow
imagine the production of threads and cloth, prints on
ceramics — specifics of the latter, needles — for clothes
making. The osteological collection and leather making
tools indicate leather and fur making; awls, sewings,
and, rarely, piercers — further processing of the raw
material. Leather / fur or thick cloth outfit is marked
with a button made of the half of a spindle.
The elements of the belt set (buckles, endings, ringsdistributors),
although a part of them could belong to
the horse harness, bags etc., remained better and allow
analyze this very specifics of the outfit, especially
in view of the whetstones, steel fire strikers and the
rest, which had been worn on belts before appearance
of pockets in XVII—XVIII cent. Not fully indentified
remains the fragment of bronze item which can be attributed
to either front plate of bronze bag buckle or
one of the variety of Christian incense burner.
Substantial supplement of an outfit are the adornments.
Aside from the items made of glass, among
which, unexpectedly, there are a plenty of bracelets’
fragments, and of amber produced at the settlement,
it is necessary to mention a range of metal items. They
are temple rings, earrings, necklaces. Among the latter
prevailing are the ones produced within the settlement.
Together with the glass and amber, the necklaces
included mineral components. Fibulas collected on
the site have the analogies from the Baltic lands, the
same relates to the other items. Arms and hands jewels
are represented with bracelets and signet rings.
In spite of the rather small researched area of
1041 m2 and so, not too extensive collection of the mentioned
findings, its analysis tracks the original peculiarities
of the researched settlement.
Keywords: medieval times, non-fortified settlements
Kyiv’s outskirts, outfit, belt set, bag buckles,
adornments, Khodosivka-Roslavske.